Housing issues in Nuuk (Greenland) and how to get students involved - Sørensen, Jane; Willumsen, Ulla (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2013)
In this essay, we discuss housing policy in Nuuk (Greenland), which is characterised by disparity, undemocratic decision-making, and lack of open, frank discussion. Greenland has a culture of conflict avoidance and reluctance to accept criticism, due to its small population and its cultural traditions. Moreover, the city council’s housing policy has to take both the affluent and the less well-off into consideration. The latter, however, find it harder to influence policy-making. At the Ilinniarfissuaq (Institute for Learning) in Nuuk, we want our future teachers to take part in the development of society and in public debates over social issues. They should in turn be able to teach their students to get involved and to take a stand in debates. But how can we help these future teachers develop a critical view of housing policy without feeling oppressed and powerless? We tried to solve this problem through a technical solution—a GIS program. This program forced our teacher trainees to take a position and express their opinions.